2020
DOI: 10.18280/ijdne.150405
|View full text |Cite
|
Sign up to set email alerts
|

The Stimulated Growth of Tissue Cultured Banana and Slipper Orchid as Exposed to Extremely Low Frequency Electromagnetic Field

Abstract: Extremely low frequency electromagnetic field (ELF-EMF) naturally occurs in the environment as the use of electricity become more intense, thus affecting the life of all organisms includes plants, both positive and negative way. The study of to determine the real effect of EFL-EMF was conducted using tissue culture plants in two different plants, banana (Musa acuminata cv. Barangan) and orchid (Paphiopedilum rothscildianum). Banana and orchid plantlets were exposed to 6 and 12 mT ELF-EMF for 0.5, 1, 2, and 4 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Shabrangi et al [29] reported that treatment with 3 mT and 10 mT ELF magnetic fields for four hours resulted in significantly increased catalase (CAT) and ascorbic peroxide (APX) activity in root and shoot tissues. Prihatini et al [30] reported that the 6 mT magnetic field treatment for 0.5 hours increased banana shoot growth by 27.3%. This study found that the treatment of a time-varying unidirectional magnetic field with a flux density of 0.1-0.3 mT accelerated the emergence of sprouts.…”
Section: Discussionmentioning
confidence: 99%
“…Shabrangi et al [29] reported that treatment with 3 mT and 10 mT ELF magnetic fields for four hours resulted in significantly increased catalase (CAT) and ascorbic peroxide (APX) activity in root and shoot tissues. Prihatini et al [30] reported that the 6 mT magnetic field treatment for 0.5 hours increased banana shoot growth by 27.3%. This study found that the treatment of a time-varying unidirectional magnetic field with a flux density of 0.1-0.3 mT accelerated the emergence of sprouts.…”
Section: Discussionmentioning
confidence: 99%